A performance musical como interação: dialogismo, significados e sucesso - Carla Jean Seibert (2010)
How does music performance communicate? What does it communicate? How does one define a successful music performance? The present thesis aims to discuss and search for answers to these fundamental questions about music performance from the perspective that performance is essentially a social interaction. For this purpose, a theoretical description of music performance is presented based on the concept of dialogism, the unifying idea of the writings of philosopher Mikhail Bakhtin. The study of the dialogism of verbal and non-verbal discourses elucidates the ways in which music performance communicates. Contextualized in the research on dialogism and music performance, the description of music performance as communication is made to dialogue with the contributions of musicologists, anthropologists, performers and composers through indirect documentation. The relations of the individual with the other and the interactions in rituals and performances are considered in order to shed light on the possible meanings of music performance. A concept of success in music performance is suggested based on the dialogical view of artistic communication. Final reflections on the orchestration of dialogue in music performance conclude the thesis.